Aromatase gene expression and masculinization of Nile tilapia immersed in water 36 °C containing 17α-methyltestosterone - Agung Luthfi Fauzan; Dinar Tri Soelistyowati; Muhammad Zairin Junior; Dian Hardiantho; Mia Setiawati; , Alimuddin (Jurnal Akuakultur Indonesia)
ABSTRACT